Relationship of socio-demographic factors, knowledge, attitude, and food consumption behavior among vocational high school students during COVID-19 pandemic, Indonesia - Hastuti, Nuri; Nurdjannah, Sitti; Suryani, Dyah; Suyitno, Suyitno; Tukiyo, Intan Wahyuni (Public Health of Indonesia, 2022)
Background: Maintaining a nutritious eating behavior for school children is one of the important health issues to be carried out during the current COVID-19 pandemic. The roles of parents, teachers, and health workers are necessary for school children. Objective: This study aimed to determine socio-demographic factors, knowledge, attitude, and food consumption behavior among vocational high school students during the COVID-19 Pandemic in the Municipality of Sleman, Indonesia. Methods: Cross-sectional design was employed among 84 students selected using purposive sampling. Data were collected in September 2021 using validated questionnaires. Chi-square test and multi logistic regression were used to examine associations between independent variables and food consumption behavior. Results: The majority of the respondents were females (94%), and the range of age of all the respondents was 15-18 years old. The multi logistic regression showed that the students who had low family income (Adj. OR = 4.38, 95% CI = 1.26-15.19), poor knowledge (Adj. OR = 8.39, 95% CI = 2.10-33.52), and had no roles of parent (Adj. OR= 5.45, 95% CI = 2.37-23.43) statistically significantly had poor food consumption behavior. Conclusion: The main variables that significantly influenced food consumption behavior in vocational high school students were level of knowledge, family income, and the role of parents. This study may serve as input for public health decision-makers to improve health promotion to the students in the school.